A Bifunctional Luminescent Metal–Organic Framework for the Sensing of Paraquat and Fe3+ Ions in Water. Issue 20 (3rd July 2019) - Chen, Hongjuan; Fan, Peng; Tu, Xingxin; Min, Hui; Yu, Xianyong; Li, Xiaofang; Zeng, Ju‐Lan; Zhang, Shaowei; Cheng, Peng
Abstract: The hydrothermal reaction of Zn 2+ ions with a mixture of two ligands, Hcptpy and H3 btc (Hcptpy=4‐(4‐carboxyphenyl)‐2, 2′:4′, 4′′‐terpyridine; H3 btc=1, 3, 5‐benzenetricarboxylic acid), led to the formation of a 3D metal–organic framework (MOF) with 1D channels, [Zn2 (cptpy)(btc)(H2 O)] n (1 ), which was structurally characterized by using single‐crystal X‐ray diffraction (SXRD). In MOF1, two independent Zn 2+ ions were interconnected by btc 3− ligands to form a 1D chain, whilst adjacent Zn 2+ ions were alternately bridged by cptpy − ligands to generate a 2D sheet, which was further linked by 1D chains to form a 3D framework with a new (3, 3, 4, 4)‐connected topology. Furthermore, compound1 also exhibited excellent stability towards air and water and, more importantly, luminescence experiments indicated that it could serve as a probe for the sensitive detection of paraquat (PAQ) and Fe 3+ ions in aqueous solution. Abstract : Two strings to one′s bow : A 3D mixed‐ligand‐based metal–organic framework with 1D channels, which adopts a new (3, 3, 4, 4)‐connected topology, has been hydrothermally synthesized. Interestingly, compound1 is a potential probe for the sensitive detection of paraquat and Fe 3+ ions in aqueous solution. More importantly, compound1 has demonstrated remarkable stability towards air and water, as well as acidic and alkaline conditions.